Computer-assisted chromosome mapping by protoplast fusion in Staphylococcus aureus. - Stahl, M L (1983)
Protoplasts of genetically marked derivatives of Staphylococcus aureus NCTC 8325 were fused with polyethylene glycol and regenerated without selection. Recombinants possessing one specific resistance marker from each parent were selected from the regenerated population and scored for seven or eight unselected markers. The results of these 9- and 10-factor crosses were entered directly into a programmed microcomputer from prescored replica plates. The data then were condensed into an array of phenotypes, together with the frequency with which each occurred. Further analyses by computer included the calculation of coinheritance frequencies for all possible pairs of markers; after entering a proposed order for the markers being analyzed, the minimum number of crossover events required to generate each phenotypic class was calculated. The linkage relationships of markers, based on the protoplast fusion data, were entirely consistent with the linkage relationships of markers already known to exist within each of the three linkage groups previously defined by transformation. The fusion data defined an arrangement of the three linkage groups into a circular chromosome map and predicted the approximate location of four previously unmapped markers (tet-3490, fus-149, purC193::Tn551, and omega [Chr::Tn551]42) on this map.